Structure–activity relationship of novel macrocyclic biased apelin receptor agonists. Issue 2 (7th December 2016) - Murza, Alexandre; Sainsily, Xavier; Côté, Jérôme; Bruneau-Cossette, Laurent; Besserer-Offroy, Élie; Longpré, Jean-Michel; Leduc, Richard; Dumaine, Robert; Lesur, Olivier; Auger-Messier, Mannix; Sarret, Philippe; Marsault, Éric
Abstract : Apelin is the endogenous ligand for the G protein-coupled receptor APJ and exerts a key role in regulating cardiovascular functions. Abstract : Apelin is the endogenous ligand for the G protein-coupled receptor APJ and exerts a key role in regulating cardiovascular functions. We report herein a novel series of macrocyclic analogues of apelin-13 in which the N- and C-terminal residues as well as the macrocycle composition were chemically modified to modulate structure–activity relationships on the APJ receptor. To this end, the binding affinity and the ability to engage G protein-dependent and G protein-independent signalling pathways of the resulting analogues were assessed. In this series, the position and the nature of the C-terminal aromatic residue is a determinant for APJ interaction and β-arrestin recruitment, as previously demonstrated for linear apelin-13 derivatives. We finally discovered compounds1, 4, 11 and15, four potent G protein-biased apelin receptor agonists exhibiting affinity in the nanomolar range for APJ. These macrocyclic compounds represent very useful pharmacological tools to explore the therapeutic potential of the apelinergic system.